2020
DOI: 10.1002/jgc4.1323
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of the Genetic Counseling Outcome Scale for autism spectrum disorders and related conditions

Abstract: The genetics care pathway experienced by families affected by autism spectrum disorder (ASD) around the time of diagnosis is currently uncharacterized and potentially variable across contexts. The lack of consensus on outcome measures to capture the impact of genetic services for these families shows a gap in understanding and optimizing this genetics care pathway. The Genetic Counseling Outcome Scale (GCOS‐24) is a validated outcome measure of clinical genetics services. The current study aims to adapt and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Psychometric analysis of the GCOS‐24, in a population of individuals with genetic conditions, revealed good internal consistency, test–retest reliability, sensitivity to change, and evidence of construct validity (McAllister, Wood, et al, 2011 ). For the purpose of our study, we utilized an adapted version of the GCOS‐24, the mGCOS‐24, as previously described (Yusuf, Peltekova, Savion‐Lemieux, Frei, Joober, et al, 2020 ). Higher scores indicate greater degree of empowerment.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychometric analysis of the GCOS‐24, in a population of individuals with genetic conditions, revealed good internal consistency, test–retest reliability, sensitivity to change, and evidence of construct validity (McAllister, Wood, et al, 2011 ). For the purpose of our study, we utilized an adapted version of the GCOS‐24, the mGCOS‐24, as previously described (Yusuf, Peltekova, Savion‐Lemieux, Frei, Joober, et al, 2020 ). Higher scores indicate greater degree of empowerment.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…First, we assessed diagnostic yield (clinical utility) in a population‐based sample of families with an affected child, as they underwent diagnostic assessment. Second, we examined empowerment of parents (personal utility) around the time of clinical genetic testing for the child, using a modified version of the GCOS‐24 (mGCOS‐24) that we recently adapted and validated for use in parents of children with NDDs (Yusuf, Peltekova, Savion‐Lemieux, Frei, Joober, et al, 2020 ). Finally, we explored child, family, and health services factors proposed as potential predictors of empowerment in the context of genetic testing for ASD and related NDD (Kasparian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only a portion of individuals with prevalent genetic abnormalities such as Down or Fragile X syndrome are co-diagnosed with ASD [3], demonstrating the lack of specificity of a genetic diagnosis. The lack of good-quality outcome studies for using a structural genetic analysis in the clinical ASD field is emphasized by the need for quantitative outcome measures [26]. Although clinical improvements in management are possible with this information, this usually requires an experienced geneticist to comprehensively interpret complex genetic information [27].…”
Section: Structural Dna Alterationsmentioning
confidence: 99%
“…Prior research has suggested several complexities related to genetic testing and counselling. Family members have reported, for instance, wide variations in experiences of pre‐test counselling and extents of post‐test counselling concerning autism (Yusuf et al, 2021). Patients in Ireland with rare diseases, for example, often experienced delays in obtaining timely genetic counselling to assist with psychosocial stresses.…”
Section: Introductionmentioning
confidence: 99%